TREN DAN PETA RISET ISLAMIC PARENTING : ANALISIS SCIENTOMETRIK LITERATUR GLOBAL 2017-2025 - Anggara Dias, Naufal; Anwar, Chairul; Hijriyah, Umi; Saputra, Amri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to map the trends, structure, and development of Islamic Parenting research in the global scientific literature from 2017 to 2025 using a scientometric approach. The research method employed is a bibliometric analysis of international journal articles relevant to the topic of Islamic parenting. Bibliographic data were collected based on specific inclusion criteria and analyzed using R software with the Bibliometrix package through the Biblioshiny interface. The analysis covers general publication characteristics, authors’ and institutions’ productivity and scientific impact, journal source distribution, citation patterns, and thematic structure mapping through various visualizations.The results indicate that research on Islamic Parenting has experienced positive growth but remains at an early to intermediate stage of scientific development. Publications are predominantly characterized by normative-educational themes with relatively limited topic diversification, while international collaboration and citation impact remain moderate. The thematic mapping positions Islamic Parenting as a basic theme with high relevance but requiring deeper conceptual and empirical exploration. This study concludes that Islamic Parenting research holds significant potential for further development through interdisciplinary, contextual, and collaborative approaches, thereby strengthening its theoretical and practical contributions to the study of Muslim family parenting in the contemporary era.